PENDIDIKAN MULTIKULTURAL: SUATU KONSEP, PENDEKATAN DAN SOLUSI - Kuswaya Wihardit (LPPM Universitas Terbuka, 2010)
Indonesia is a plural nation which consists of different ethnics, races, languages, customs, religions, and cultures. Indonesian society is also recognized as multicultural society with diversed background of cultures and religions. Conceptually, multiculturalism refers to country profile as a plural nation and multicultural society. Citizens would appreciate plurality and multiculturalism based on the equity principle.Multiculturalism as a concept of diversity and equity should be accomodated in the national education system. It should be reflected in the curriculum. Besides, the school has opportunity to develop its school curriculum (KTSP) integrating multicultural elements.Citizenship Education subject has the functions to integrate and develop multiculturalism issues in selected topics such as unity, equity, human rights, democracy, justice, and law. Other subjects integrate the issues into the teaching and learning process focusing issues of gender, ethnicity, and religion. Multicultural education is intended for develoving national character which promote students interactivity of different social cultural background. It develops in students emphaty through the observation of their attitude, perceptions, and views. In addition, it also develops student appreciation of multicultural differences, values, dan needs.